2019
DOI: 10.1017/dsi.2019.218
|View full text |Cite
|
Sign up to set email alerts
|

Industry Trends to 2040

Abstract: The engineering design community needs to development tools and methods now to support emerging technological and societal trends. While many forecasts exist for technological and societal changes, this paper reports on the findings of a workshop, which addressed trends in engineering design to 2040. The paper summarises the key findings from the six themes of the workshop: societal trends, ways of working, lifelong learning, technology, modelling and simulation and digitisation; and points to the challenge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 5 publications
(3 reference statements)
0
18
1
Order By: Relevance
“…Servitization refers to "transformation toward a service-dominant logic, which stresses the importance of providing solutions rather than products" [72]. In contrast to findings in literature reviews [57,58], the interviewed companies did not indicate that servitization is a future competitive strategy and an important source of profit, despite the fact that it is less hard to imitate.…”
Section: Capabilities In Product Development For Realizing the Potentcontrasting
confidence: 56%
See 1 more Smart Citation
“…Servitization refers to "transformation toward a service-dominant logic, which stresses the importance of providing solutions rather than products" [72]. In contrast to findings in literature reviews [57,58], the interviewed companies did not indicate that servitization is a future competitive strategy and an important source of profit, despite the fact that it is less hard to imitate.…”
Section: Capabilities In Product Development For Realizing the Potentcontrasting
confidence: 56%
“…This study showed a need for new and complemented education in industry on the three areas in order to meet the possibilities, needs, and expectations from society. Therefore, strategic measures from a societal level in offering multidisciplinary education, as well as long-life learning efforts, should be prioritized, as also discussed in Eckert et al [72]. A higher educational level can both generate new unique solutions and improve the company's internal work processes, and, together with support companies and suppliers, be prepared and more proactive in the transition towards a more digitalized and sustainable society.…”
Section: Capabilities In Product Development For Realizing the Potentmentioning
confidence: 99%
“…before, as products are becoming more complex and interdisciplinary, companies aim to deliver holistic user experiences based on new business models and the development processes are becoming more global (Nguyen, Müller & Stark 2013;Kimita et al 2015;Eckert et al 2019;Wichmann, Eisenbart & Gericke 2019). For example, Industry 4.0 will require a greater integration between software, hardware and electronics.…”
Section: /22mentioning
confidence: 99%
“…Data analysis, Big data and AI are wildly recognised trend areas in engineering, [6], [16], [17] and engineering companies are bracing themselves to respond and work with data experts.…”
Section: Working With Data Expertsmentioning
confidence: 99%